Key trends in feeding the world, 1970-1995 - Fritschel, Heidi; Pandya-Lorch, Rajul; Rose, Barbara (International Food Policy Research Institute, 1996)
A Guide to the 2020 Vision Video 2020 Hindsight: Successes, Failures, and Lessons Learned in Feeding the World, 1970-95, which presents a visual overview of recent efforts to feed the world. This guide tells the story in slightly more detail and concludes with questions that may be used to stimulate discussion.